Pengaruh Social Media Marketing Bloomka dalam Pandemi COVID-19 terhadap Minat Beli Konsumen - Agnes Putu Kezia Hanada (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstract The COVID-19 pandemic has increased the use of social media, most of the brands carry out marketing activities through social media. One brand that uses marketing techniques via social media is Bloomka. Bloomka is a brand in the beauty sector that develops its business by utilizing Instagram. The purpose of this study is to determine the impact of Bloomka's social media marketing during the COVID-19 pandemic on consumers' intention to buy as well as to find out how much the influence was generated. Researchers used this type of quantitative research with survey methods to collect data. The data collection technique was carried out by distributing questionnaires to 400 respondents, using a purposive sampling technique. This study shows there is a positive impact of social media marketing on consumers' intention to buy during the COVID-19 pandemic by 43,7%. The result of this research can be used as an example for online businesses to maximize marketing through social media to increase consumers' intention to buy